INDICATORS OF FERROUS METALLURGY OF THE CIS COUNTRIES AND FORMER USSR TO THE YEAR 2000 - V. I. Timoshpolskii; A. I. Trusova (Литьë и металлургия, 2018)
Over the past decades, the world’s steel industry has implemented two areas of its development: construction and commissioning of modern mini-plants; modernization of enterprises with a full metallurgical cycle. Despite a number of advantages of mini-plants, the global growth of steel production since 2000 has been largely due to the construction and commissioning of Converter production in China. The article presents data on the development and restructuring of metallurgical enterprises with a full cycle, primarily in the conditions of ferrous metallurgy of the CIS and former USSR. The main technological equipment for metallurgical processing, including the production of iron, steel, blanks, finished products, as well as the volume of production per year for the leading enterprises of the CIS and the former USSR was described in the article.It is also noted that in connection with the annual re-equipment of the production capacity of the main workshops in the steel industry of the former USSR, the training of highly qualified engineers and workers was the most important task of the state.